A Comparative Interrupted Times Series on the Health Impact of Probiotic Yogurt Consumption Among School Children From Three to Six Years Old in Southwest Uganda - Westerik, Nieke; Nelson, Arinda; Wacoo, Alex Paul; Sybesma, Wilbert; Kort, Remco (Frontiers in Nutrition, 2020)
Introduction: Following a school milk feeding program in Southwest Uganda, we initiated a probiotic yoghurt school feeding program in the same region in 2018. In order to investigate the potential health benefits from probiotic yoghurt we conducted an observational study, where we compared effects of the consumption of locally produced probiotic yoghurt containing Lactobacillus rhamnosus yoba 2012 to milk in pre-primary schoolchildren from different schools on the occurrence of respiratory tract infections (common cold) and skin infections (e.g. tinea capitis). Method: A comparative interrupted time series over a period of three weeks of baseline followed by nine weeks of 100 ml of probiotic yoghurt or milk consumption for five days per week. In total 584 children attending five different schools were followed during consumption of probiotic yoghurt and 532 children attending five other schools during consumption of milk. Incidences of respiratory tract infection symptoms and skin infection symptoms, changes in anthropometric indicators and absenteeism were recorded.. Results: Over the course of the study period the incidence rate for common cold symptoms decreased faster in the yoghurt group than in the milk group (p = 0.09) resulting in a final RR of 0.85 (95% CI: 0.5 – 1.4) at the end of the observational period. The incidence rate of skin infection related symptoms also reduced faster in the yoghurt group compared to the milk group (p < 0.0001) resulting in a relative risk factor (RR) of 0.6 (CI: 0.4 – 0.9) at the end of the observational period. Anthropometric indicators and level of absenteeism did not show significant differences between yoghurt and milk. Conclusion: Notwithstanding the observed positive trend and effect of probiotic yoghurt on the incidences of common cold and skin infections, respectively, we consider the results of this comparative interrupted time series inconclusive due to differences in the recorded health parameters between the probiotic yoghurt and milk control groups at base line, and fluctuations over the course of the intervention period. An improved study design, with more uniform study groups, a longer intervention period and a third control group without yoghurt or milk is required to draw definitive conclusions.